Political economy and the changing global order. 3rd ed. (New York, 2006)
"Designed to introduce students to a broad range of perspectives on the rapidly changing field of international political economy, this third edition of Political Economy and the Changing Global Order offers a critical assessment of the contemporary discipline and includes a number of new articles on emerging areas of IPE, such as gender, security, environmentalism, crime, and the role of the Internet. As well, all articles from the previous edition have been updated and revised to reflect the growing tensions among globalization, regionalism, and national interests. Every chapter includes a list of suggested readings and, where appropriate, key websites, and each of the book's four sections opens with an informative introduction."